One-step production of darunavir solid dispersion nanoparticles coated with enteric polymers using electrospraying. (14th August 2015) - Nguyen, Duong Nhat; Palangetic, Ljiljana; Clasen, Christian; Van den Mooter, Guy
Abstract: Objectives: The aim of this work was to investigate the feasibility of producing darunavir (DRV) solid dispersion nanoparticles coated with an enteric polymer in one single step using electrospraying. Methods: The core-shell nanoparticles were made using coaxial electrospraying. A solution of DRV with hydroxypropyl methylcellulose in a mixture of organic solvents formed the core, while the shell was produced from an enteric polymer (Eudragit L100) dissolved in an organic solvent. The final particles were evaluated in terms of morphology, physical state, encapsulation efficiency and in-vitro dissolution. Key findings: Nanoparticles of encapsulated DRV solid dispersions within Eudragit L100 were successfully prepared with high encapsulation efficiency (90%). The enteric coating layer reduced the percentage of DRV release in acidic medium in the in-vitro dissolution test to less than 20%. Conclusions: This study showed the potential of coaxial electrospraying for encapsulating solid dispersions within core-shell structured nanoparticles.